2002
DOI: 10.1164/rccm.2109011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Allergen-induced Structural Airway Changes in Brown Norway Rats

Abstract: It remains to be fully established whether allergen-induced airway inflammation and remodeling are influenced by age. The aim of the present study was to compare allergen-induced airway changes in young and adult rats. Brown Norway rats were sensitized at 4 weeks of age (young) or 13 weeks of age (adult) and exposed to aerosolized ovalbumin (OA) or phosphate-buffered saline for 2 weeks. In both age groups OA exposure induced an increase in OA-specific Immunoglobulin E and in the number of peribronchial eosinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
3
6
1
1
Order By: Relevance
“…In a similar study, when 4-and 13-wk-old rats were compared, the younger animals had more pronounced airway functional alterations and inflammatory changes, supporting increased susceptibility at a younger age (10). In other reports, aged dogs, rats, rabbits, and mice showed a significant impairment in the generation of Th2-type allergic responses (11, 30 -34), as demonstrated in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a similar study, when 4-and 13-wk-old rats were compared, the younger animals had more pronounced airway functional alterations and inflammatory changes, supporting increased susceptibility at a younger age (10). In other reports, aged dogs, rats, rabbits, and mice showed a significant impairment in the generation of Th2-type allergic responses (11, 30 -34), as demonstrated in this study.…”
Section: Discussionsupporting
confidence: 89%
“…In the mouse there is support for these ideas based on the demonstration of defective generation of memory T cells in older mice (8) and that naive CD4 T cell function also dramatically declines with age (9). The responses to various stimuli (10,11) and the rate of repair (12)(13)(14) may also show a degree of age dependency.…”
mentioning
confidence: 99%
“…In young animals, highly significant WAt/Pbm differences were found in the small and medium IA, while in adult rats the medium and predominantly large IA differed from controls in terms of this parameter. This result is very similar to the findings of Palmans et al [18], who evaluated large IA exclusively and found a significant WAt/Pbm increase only in adult rats.…”
Section: Discussionsupporting
confidence: 92%
“…Fewer authors, however, have attempted to produce a model of chronic bronchial asthma with wall remodeling [17]. There is, to our knowledge, only one paper describing the differences in remodeling changes in two animal age groups and thus simulating developing asthma in children [18]. That study showed more pronounced airway remodeling at a young age; nevertheless, the authors examined only large airways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation